Science Learning culture: An Ethnographic Study of a Public school in Nepal - Reshmi, Dhan Bahadur (Butwal Campus Journal, 2025)
Based on the rural Magar community area public school context, this paper aims to explore pedagogical strategies to empower indigenous learners, such as Magar students’ science learning. In this ethnographic study, grade ten students and teachers who are involved in teaching in the same grade are purposively selected as the co-researchers for data generation. Fieldwork observation, interviews, and document analysis were research approaches, and a descriptive qualitative design was used to explore the reflections. The findings were four attributes: presage attribute, context attributes, process attributes, and product attributes. However, community observation (context attributes) and product attributes were skipped due to the research technical issues. The discussion of this study was framed by Habermas’ theory of cognitive interests. Based on the discussion, the study concluded that the existing learning culture attributes are conventional and need to be upgraded through school infrastructural development, implementing policy provisions, and integrating culturally responsive STEAM approaches in teaching strategies to empower the learning culture of science education for marginalized learners.